THE CLASSIFICATION OF THE NAMES OF POPULATION SETTLEMENTS IN SURKHANDARYA REGION BY THE HISTORICAL FACTORS - Umarova M. H; Esanov N. A; Xolmatov Z. M; Turaev Q. T (International Engineering Journal For Research & Development, 2020)
When analyzing place names on the basis of historical criteria, it is studied to which lexical-geographical layer the toponym belongs. The peculiarities of the names of geographical places from different languages are taken into account. Including Turkish, Persian, Tajik, Arabic, new names were considered.